Taking Medvedev at his Word: The Russian president's proposal for an international energy accord and the Energy Charter Treaty - Kirsten Westphal (Stiftung Wissenschaft und Politik (SWP), 2009)
In February 2009, the Russian president presented his concept for an international framework agreement in the energy sector. Yet up to now, the proposal has passed largely without comment. This is partly related to the 2009 Russian-Ukrainian gas conflict, after which the document was seen as a further attempt to undermine the Energy Charter Treaty. Then in July 2009, the Russian government decided to withdraw from the Energy Charter Treaty. At the present stage, Europe should take Medvedev at his word. Now more than ever, his proposal should be used as a catalyst to flesh out the details of a global energy treaty that goes beyond existing documents such as the 2008 G8 Declaration on Global Energy Security
Keywords: 320